Advanced paternal age and childhood cancer in offspring: A nationwide register‐based cohort study. Issue 11 (23rd March 2017) - Urhoj, Stine Kjaer; Raaschou‐Nielsen, Ole; Hansen, Anne Vinkel; Mortensen, Laust Hvas; Andersen, Per Kragh; Nybo Andersen, Anne‐Marie
Abstract : Cancer initiation is presumed to occur in utero for many childhood cancers and it has been hypothesized that advanced paternal age may have an impact due to the increasing number of mutations in the sperm DNA with increasing paternal age. We examined the association between paternal age and specific types of childhood cancer in offspring in a large nationwide cohort of 1, 904, 363 children born in Denmark from 1978 through 2010. The children were identified in the Danish Medical Birth Registry and were linked to information from other national registers, including the Danish Cancer Registry. In total, 3, 492 children were diagnosed with cancer before the age of 15 years. The adjusted hazard ratio of childhood cancer according to paternal age was estimated using Cox proportional hazards regressions. We found a 13% (95% confidence interval: 4–23%) higher hazard rate for every 5 years advantage in paternal age for acute lymphoblastic leukemia, while no clear association was found for acute myeloid leukemia (hazard ratio pr. 5 years = 1.02, 95% confidence interval: 0.80–1.30). The estimates for neoplasms in the central nervous system suggested a lower hazard rate with higher paternal age (hazard ratio pr. 5 years = 0.92, 95% confidence interval: 0.84–1.01). No clear associations were found for the remaining childhood cancer types. The findings suggest that paternal age is moderately associated with a higher rate of childhood acute lymphoblastic leukemia, but not acute myeloid leukemia, in offspring, while no firm conclusions could be made for other specific cancer types. Abstract : What's new? Do older fathers impart more mutations to their children, leading to more frequent childhood cancer? To investigate, these authors looked at data from a cohort of children born in Denmark during the years 1978–2010. They found a higher rate of acute lymphoblastic leukemia, but not acute myeloid leukemia, among children born to fathers over age 45 years. Conversely, children with older fathers seemed to experience fewer central nervous system neoplasms. Other childhood cancers showed no clear link to the father's age.